PENGEMBANGAN BAHAN PEMBELAJARAN MATA KULIAH OLAHRAGA DAN SENAM ANAK USIA DINI BERBASIS NILAI-NILAI ISLAM - Abdul Rahman; Hartati, Meri (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research was to develop appropriate teaching materials for Physical Education and Gymnastics for Early Childhood based on Islamic values, tailored to meet the needs of both lecturers and students. This study used data collection techniques including observation, interviews, and questionnaires, and applied the Research and Development (R&D) method with the Borg and Gall approach, which consists of five stages: (1) preliminary study, (2) product development, (3) validation, (4) feasibility testing, and (5) dissemination. The results of this study show that the teaching materials for Physical Education and Gymnastics for Early Childhood successfully integrated Islamic values. The materials received excellent feedback and were deemed highly suitable for use. This was evidenced by the validation results from experts in content, language, and media, who gave an average score of 89%, classifying the materials as highly suitable. Furthermore, the materials were tested in a small-scale trial, receiving a score of 85%, and in a large-scale trial, receiving 88%, both indicating that the materials are highly suitable for use.